2017
DOI: 10.1097/mao.0000000000001538
|View full text |Cite
|
Sign up to set email alerts
|

Intracanalicular Vestibular Schwannomas: Initial Clinical Manifestation, Imaging Classification, and Risk Stratification for Management Proposal

Abstract: We should consider observation a therapeutic modality. We valid the intrameatal staging as prognostic factor and propose a stratification of patients into low, moderate, or high risk for potential tumor growth to guide the initial management of ICVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Several authors have tried to identify features of VS that might predict future growth, growth rate and/or treatment. Most, however, looked at VS subgroups (eg VSs limited to the internal auditory canal 24,25 or non‐cystic VSs 26,27 ) used small sample sizes, 3,24,28‐33 used volume measurements to assess growth 30 or included growth rate in the first year of follow‐up in their analyses 32 . Based on findings of studies on the topic, including the current study, we might state that age and sex are no strong predictors for VS growth 4,24,29‐35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have tried to identify features of VS that might predict future growth, growth rate and/or treatment. Most, however, looked at VS subgroups (eg VSs limited to the internal auditory canal 24,25 or non‐cystic VSs 26,27 ) used small sample sizes, 3,24,28‐33 used volume measurements to assess growth 30 or included growth rate in the first year of follow‐up in their analyses 32 . Based on findings of studies on the topic, including the current study, we might state that age and sex are no strong predictors for VS growth 4,24,29‐35 .…”
Section: Discussionmentioning
confidence: 99%
“…Most, however, looked at VS subgroups (eg VSs limited to the internal auditory canal 24,25 or non‐cystic VSs 26,27 ) used small sample sizes, 3,24,28‐33 used volume measurements to assess growth 30 or included growth rate in the first year of follow‐up in their analyses 32 . Based on findings of studies on the topic, including the current study, we might state that age and sex are no strong predictors for VS growth 4,24,29‐35 . Multiple authors did find an association between VS growth or treatment and VS size at time of diagnosis, 4,24,26,36,37 balance complaints 4,26,35 or extension in the CPA 26,33,38,39 …”
Section: Discussionmentioning
confidence: 99%
“…A striking 95% of VS patients develop SNHL; additional symptoms can include tinnitus, balance difficulties, and facial paralysis (2). The conventional hypothesis regarding the mechanism underlying VS-induced SNHL is that the tumor compresses the vestibulocochlear nerve, preventing neural signals carrying hearing and balance information from traveling from the inner ear to the brain; however, evidence from multisite, large cohort studies suggests that associations between tumor size and location and SNHL severity are weak (3)(4)(5)(6)(7), and that SNHL may (4,8,9) or may not (8,(10)(11)(12)(13) worsen with tumor growth over time in VS patients. Furthermore, (1) increased outer hair cell-generated distortion product otoacoustic emission (DPOAE) thresholds are observed in VS patients with minimal SNHL, indicating that outer hair cell damage may occur as a primary event, rather than secondary to neuronal damage (14), (2) 90% of human temporal bones from patients with ipsilateral VS show hair cell and neuronal damage that do not correlate with tumor size (15), and (3) biochemically-measured and radiologically-inferred intracochlear fluid protein levels are elevated in ears from poor-hearing VS tumor patients independent of tumor size (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Younes et al. used 2 mm/year to identify the growing tumor, but no significant association was spotted between tumor growth and hearing loss ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that hearing impairment was related significantly to rapid tumor growth (≥0.10 cm 3 /year) (25). Conversely, Younes et al used 2 mm/year to identify the growing tumor, but no significant association was spotted between tumor growth and hearing loss (29).…”
Section: Tumor Growthmentioning
confidence: 99%